FEATURE OF ISLAM WHICH IS DISTINGUISHED FROM OTHER RELIGIONS - Moftah, Mohamed Omar; Abdel Gadir, Ahmed Elsaddig Dawelnor (ULUL ALBAB Jurnal Studi Islam, 2011)
The few people who do not understand the meaning of nationalism and the easiness of religions try to attack nationalism by the name of religion without comprehending the sublime meanings of Islam, which have made holy nationalism and called for easiness and facilitation. Easiness and facilitation is considered the first feature of the Islamic civilization, one aspect of its manifestations, and the first that encourages its acceptance by way of its carrying values, legislations, manners and cultural patterns. The importance of this paper is to show easiness and facilitation that Muslim civilization brought and applied in reality. Such feature is what proved such civilization’s reality and by which it won amazing bets in wars of challenge and interaction with the other world civilizations. Due to this, the inductive and historical approach has been adopted to show Islam’s easiness and facilitation. Among the results of this paper is the revelation that Islam put the first universal statement in rights of citizenship without discriminating between followers of religions, doctrines, race, or color. Also, easiness in Islam has established social solidarity: the rich give the poor; and the orphan seeks all Muslims as fathers caring for him.